Lactococcus lactis D4 Decreases NF-κB and α-SMA in Rat Models of Obstructive Jaundice - Suchitra, Avit; Alvarino, Alvarino; Darwin, Eryati; Harun, Harnavi; Rivai, Muhammad Iqbal; Sukma, Ade (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Obstructive jaundice, often due to choledocholithiasis or malignancies, leads to immune suppression, intestinal damage, and bacterial translocation, worsening outcomes. Some inflammatory mediators like nuclear factor kappa B (NF-κB), alpha-smooth muscle actin (α-SMA), and interleukin-6 (IL-6) are important in this process. Current treatments remain inadequate, highlighting the need for novel approaches. Probiotics, such as Lactococcus lactis D4 (LLD4), may help reduce inflammation and bacterial translocation, thus offering a potential therapeutic option. This study was conducted to evaluate the effects of LLD4 on NF-κB, α-SMA, and IL-6 in obstructive jaundice rat models.METHODS: This post-test randomized controlled study involved 15 male Wistar rats divided into three groups: sham, bile duct ligation (BDL), and BDL+LLD4 groups. The rats were maintained for 7–10 days, with the rats in BDL+LLD4 group received fermented milk containing LLD4 via gavage at a dose of 112 mg/20 gBW per day for 7 days. The expression levels of NF-κB, α-SMA, and IL-6 were analyzed using immunohistochemistry.RESULTS: Administration of LLD4 were able to significantly reduced NF-κB expression compared to the BDL group (40.20±21.276 vs. 53.60 ± 20.403) in obstructive jaundice rat models. Though not significant, BDL+LLD4 group showed lower α-SMA expression compared to BDL group (58.40±14.271 vs. 63.20±9.16). However, administration of LLD4 did not give any significant effect on IL-6 expression.CONCLUSION: LLD4 reduces inflammation in models of obstructive jaundice by lowering the NF-κB and α-SMA expression. This indicates that LLD4 might be potential as an adjunct therapy for reducing morbidity in obstructive jaundice cases.KEYWORDS: obstructive jaundice, bile duct ligation, Lactococcus lactis D4, NF-κB, α-SMA, IL-6